From militants to politicians Atavist Islam and the concept of democratic peace - Wyllie, James H. (Emirates lecture series, 2008)
The viability of countering Middle East terrorism by inducting extremist movements into mainstream political processes has become a contentious issue, and one high on the international security agenda. Since the early 1990s the radical, Shiite movement Hezbollah (Party of God) and, more recently, the radical Sunni, Islamist Palestinian movement Hamas, have claimed the status of normal political actors, not least good democrats. Proponents of so-called 'mainstreaming' argue that such behavior should be encouraged, regardless of some continuing bad behavior. Normal politics obliges the militant group to address the interests of a variety of people in the community and, if concerns are not met, then the militants will find their influence and reputation diminished. Does an examination of the character and behavior of these actors give any encouragement to the hope that, regardless of the atavist ideological posture embedded in the world view described above, such militants can become politicians? The cases of Hezbollah and Hamas, however, are very discouraging